The VMC Survey – XXI. New star cluster candidates discovered from infrared photometry in the Small Magellanic Cloud. Issue 1 (28th April 2016) - Piatti, Andrés E.; Ivanov, Valentin D.; Rubele, Stefano; Marconi, Marcella; Ripepi, Vincenzo; Cioni, Maria-Rosa L.; Oliveira, Joana M.; Bekki, Kenji
Abstract: We report the first search for new star clusters performed using the VISTA near-infrared YJKs Magellanic Clouds survey (VMC) data sets. We chose a pilot field of ∼0.4 deg 2 located in the South-west of the Small Magelllanic Cloud bar, where the star field is among the densest and highest reddened region in the galaxy. In order to devise an appropriate automatic procedure we made use of dimensions and stellar densities observed in the VMC data sets of the known clusters in this area. We executed different kernel density estimations over a sample of more than 358 000 stars with magnitudes measured in the three YJKs filters. We analysed the new cluster candidates whose colour–magnitude diagrams (CMDs), cleaned from field star contamination, were used to assess the clusters' reality and estimate reddenings and ages of the genuine systems. As a result 38 objects (≈ a 55 per cent increase in the known star clusters located in the surveyed field) of 0.15–0.40 arcmin (2.6–7.0 pc) in radius resulted to have near-infrared CMD features which resemble those of star clusters of young to moderate intermediate age (log( t  yr −1 ) ∼7.5–9.0). Most of the new star cluster candidates are hardly recognizable in optical images without the help of a sound star field decontaminated CMD analysis. For highly reddened star cluster candidates ( E ( B − V ) ≥ 0.6 mag) the VMC data sets were necessary in order to recognize them.